Pemanfaatan Kearifan Lokal sebagai Folk Media untuk Komunikasi Krisis Bencana - Andung, Petrus Ana; Uding, Ermenilda Putri; Levis, Leta Rafael (Universitas Prof. Dr. Moestopo (Beragama), 2024)
Kupang Regency, East Nusa Tenggara (NTT) Province is categorized as a natural disaster-prone area with various threats. Based on BNPB data, Kupang Regency is among the 10 high-risk districts in NTT Province during 2015-2022, with a disaster risk index value of 173.50 in 2022, which has increased by 5.02 compared to 2020. The results of the pre-research found that the communities in Merbaun and Toobaun villages, Kupang Regency have various hereditary local wisdom in managing nature. These local wisdoms are believed to have the potential to become traditional communication tools for disaster mitigation to make the community disaster resilient. Therefore, this research aims to explore the forms of local wisdom that act as folk media for disaster crisis communication and build a crisis communication model through the utilization of local wisdom. This research uses a constructivistic paradigm with a qualitative research type. The research method uses a case study with data collection techniques of in-depth interviews, and involved observation. The data analysis technique uses the Miles Huberman interactive model. The results showed that the community empowered local wisdom as a traditional communication tool for the benefit of disaster crisis communication. These folk media can be classified into several types, namely shouting, climate-friendly agricultural systems, traditional early warning systems, and oral and written customary laws.